1998
DOI: 10.1086/515233
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Insertion Element, IS1548, in Group B Streptococci, Predominantly in Strains Causing Endocarditis

Abstract: Hyaluronidase has been postulated to be a virulence factor in group B streptococci (GBS). No hyaluronidase activity was found in 15 of 50 GBS isolates from adults studied. Most of these hyaluronidase-negative strains belonged to serotype III. In strains lacking hyaluronidase activity, an insertion of 1317 nucleotides was found in the hyaluronidase gene. The fragment was cloned and sequenced and found to have characteristics of a novel insertion sequence, designated IS1548. As well as in GBS serotype III, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
91
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 40 publications
8
91
0
1
Order By: Relevance
“…Although phenotypically cryptic, IS elements may influence the transcription of genes (Mahillon & Chandler, 1998) or directly inactivate genes into which they become inserted (Granlund et al, 1998 ;Ziebuhr et al, 1999). Our search of the available parts of the genome sequence of JP2 clone strain HK1651 revealed close proximity between each of the two IS elements and several housekeeping genes, but no example of inserts within an identified ORF (Fig.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although phenotypically cryptic, IS elements may influence the transcription of genes (Mahillon & Chandler, 1998) or directly inactivate genes into which they become inserted (Granlund et al, 1998 ;Ziebuhr et al, 1999). Our search of the available parts of the genome sequence of JP2 clone strain HK1651 revealed close proximity between each of the two IS elements and several housekeeping genes, but no example of inserts within an identified ORF (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Upon integration IS elements may modulate the expression of neighbouring genes and, thereby, influence the phenotype of a bacterium. This phenomenon is of particular medical interest when it involves antibiotic resistance or pathogenic potential (Granlund et al, 1998 ;He et al, 1999 ;Hernandez-Alles et al, 1999 ;Preston et al, 1999 ;Sawada et al, 1999 ;Simpson et al, 1999 ;Ziebuhr et al, 1999). Furthermore, two copies of an IS element may act in concert, rendering the intervening region mobile as has been found for certain pathogenicity islands (Hacker et al, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…IS1548 is also widespread in S. pyogenes isolates, and present in S. dysgalactiae subsp. equisimilis (Granlund et al, 1998; Table 1). …”
Section: Mobile Genetic Element Of the Isas1 Familymentioning
confidence: 99%
“…These contradictory reports point out that the exact involvement of HylB in systemic infections needs further investigations (Bohnsack et al, 2001;Musser et al, 1989;Rojo et al, 2008). IS1548 possesses another preferential insertion target just upstream of the lmb gene encoding a bifunctional laminin-binding protein/zinc-binding protein (Granlund et al, 1998(Granlund et al, , 2001; Fig. 1).…”
Section: Mobile Genetic Element Of the Isas1 Familymentioning
confidence: 99%
“…Differences in pathogenic potential among subpopulations of S. agalactiae have been disputed. Musser et al (1989) identified a high-virulence clonal type of S. agalactiae serotype III in a collection of strains from the USA, Quentin et al (1995) found that among French isolates three clonal families were responsible for the majority of invasive disease in neonates and Granlund et al (1998) described an association between strains characterized by the presence of an insertion element within the hyaluronidase gene and endocarditis. We found that a population of S. agalactiae strains isolated in Denmark was predominantly clonal and there was no evidence of association between specific evolutionary lines and neonatal disease (Hauge et al, 1996).…”
Section: Introductionmentioning
confidence: 99%